Efektivitas Enkapsulasi Nano Kitosan Serai Dapur dalam Meningkatkan Depolarisasi Mitokondria pada Sel Kanker HSC-3 - Komariah, Komariah; Moksidy, Jenyfer Ignatia; Nugroho, Didi; Ranggaini, Dewi; Anggraeni , Rezky; Halim , Johni (Universitas Borneo Lestari, 2025)
Oral cancer ranks 12th among the most common types of cancer worldwide, with a prevalence of approximately 25%-40% occurring on the lateral borders and the underside of the tongue. Conventional therapies often cause side effects that damage normal cells, prompting the use of safer natural alternatives, such as Cymbopogon citratus (lemongrass). The active compounds in lemongrass leaves can enhance the production of reactive oxygen species (ROS), which trigger apoptosis through the depolarization of mitochondrial membrane potential (MMP). To improve the stability of these active compounds, they are encapsulated with chitosan, which is modified into nanoparticles to enhance diffusion through cell membranes, thereby increasing their effectiveness as anticancer agents. This study involved nine groups, including a negative control, a positive control (doxorubicin), nano chitosan, lemongrass extract, and five treatment groups with various encapsulation concentrations (100%, 75%, 50%, 25%, and 12.5%). The results showed that nano chitosan encapsulation of lemongrass extract significantly increased MMP depolarization compared to the control. The depolarization effect increased with higher encapsulation concentrations, with the lowest red fluorescence intensity observed at the 100% concentration, indicating the highest level of depolarization in HSC-3 cells.